Food science at your table: the use of turmeric flour as an antioxidant-rich ingredient to improve healthiness in whole fresh pasta (Research, Society and Development, 2021)
Fresh pasta with whole wheat flour (WWF) presents healthiness, but the consumer is not used to its consumption, due to the dark color. Therefore, the use of regional ingredients, which may change its color, could be an option to stimulate its use and daily consumption. The objective of this study was to evaluate the technological and antioxidant capacity of the fresh pasta elaborated with 51% WWF (49% Refined Wheat flour - RWF) (Control, M0) and the partial replacement of RWF by turmeric (Curcuma longa) flour (TF) at 3, 6 or 9% (respectively M1, M2 and M3). The data were analyzed by ANOVA and Tukey test (p-value